Analysis of Abnormal Causes and Renovation Measures for Voltage Monitor Board of Light Triggered Thyristor in Zhaoqing Converter Station. (October 2019) - Wang, Z; Feng, L
Abstract: In September 2018, 25 thyristor voltage monitor (TVM) boards of the Y4 valve of Pole 2 in Zhaoqing converter station did not have feedback signal. In order to make clear the root cause of this incident, the paper draws the detailed schematic diagram of the TVM board of converter valve in Zhaoqing station, and then studies the working principle of the TVM board and its feedback signal circuits, and analyzes the information interchange among all the functional modules. The pulse generation of positive voltage signal, negative voltage signal and overvoltage signal of the board are dissected. Then the equivalent circuit of each functional module is established to deduce the real reason of TVM board abnormality by quantitative calculation. Then the optimized scheme of TVM board circuit is proposed. Finally, comparative tests between the original circuit and the optimized circuit are carried out with the power supply of 459V RMS sinusoidal voltage and 7kV magnitude overvoltage respectively. The results show that the analysis of the TVM board working principle is correct, and the optimized scheme of TVM board circuit is effective.